Religious diversity and pluralism. Inter-religious relations in globalization - Petrov, George Daniel; Croitoru, Mihai Marian (Technium Social Sciences Journal, 2022)
When we talk about society, we cannot fail to notice the existence in public life of what we define as religious pluralism. Can it be said that today's society cannot be fully defined outside religious pluralism? Can modern man belong to a society without consciously or unconsciously taking part in the implications of inter-religious relations in a world of constant globalization? These are open questions that can be answered from many fields such as sociological, theological, political and others. Understanding this phenomenon gives rise to factors that determine the values of a society that can bring harmony between people to the fore.